THE AFGHAN CRISIS AND THE 2011 PROBLEM: WHAT NEXT? - MAKHMUDOV, Rustam (CENTRAL ASIA AND THE CAUCASUS, 2010)
This May, President Obama confirmed that his country had embraced a new strategy in Afghanistan by saying: “The U.S. can start withdrawing troops from Afghanistan in July 2011.” The White House supported the new strategy with a 30-thousand-strong additional contingent in this country and a bigger military budget.The analytic community was left to guess: would the withdrawal be complete, or would it introduce new approaches to an old problem? What was behind the new president’s initiative? How would it affect Central and South Asia, to say nothing of the global geopolitical balance of power?These and a multitude of other questions are born by the fact that as part of the U.S. foreign policy orbit Afghanistan is no longer a “thing in itself” (to borrow a philosophical term), but just one element among many others in the intricate geopolitical and geo-economic mosaic.It is beyond the scope of one article, no matter how long it is, to deal with all the aspects of the current processes, therefore I have limited myself to the financial and economic issues behind the planned withdrawal, the impact of thePakistani factor, and the possible consequences as seen from Moscow, Beijing, Tehran, and the Central Asian capitals.